A serious game for teaching Java cybersecurity in the industry with an intelligent coach - Casqueiro, Luís Afonso Maia Rosa (2021)
Cybersecurity as been gaining more and more attention over the past years. Nowadays we continue to see a rise in the number of known vulnerabilities and successful cyber-attacks. Several studies show that one of the causes of these problems is the lack of awareness of software developers. If software developers are not aware of how to write secure code they can unknowingly add vulnerabilities to software. This research focuses on raising Java developers cybersecurity awareness by employing a serious game type of approach. Our artifact, the Java Cybersecurity Challenges, consist of programming exercises that intend to give software developers hands-on experience with security related vulnerabilities in the Java programming language. Our designed solution includes an intelligent coach that aims at helping players understand the vulnerabilities and solve the challenges. The present research was conducted using the Action Design Research methodology. This methodology allowed us to reach a useful solution, to the encountered problem, by applying an iterative development approach. Our results show that the developed final artifact is a good method to answer the defined problem and has been accepted and incorporated in an industry training program. This work contributes to researchers and practitioners through a detailed description on the implementation of an automatic code analysis and feedback process to evaluate the security level of the Java Cybersecurity Challenges.